2002
DOI: 10.1002/1521-3919(20020901)11:7<751::aid-mats751>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Conformation-Dependent Sequence Design of HP Copolymers: An Algorithm Based on Sequential Modifications of Monomer Units

Abstract: We present a new modification of the so‐called conformation‐dependent sequence design scheme for HP copolymers which was proposed several years ago (H and P refer to the hydrophobic and polar monomer units, respectively). New method models the real chemical experiments more realistically. We performed Monte Carlo computer simulations using the bond‐fluctuation model for protein‐like copolymers obtained by means of the new “iterative” method and compared the results with those obtained for originally proposed “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Presently, much attention has been paid to the coil-globule transition of a polymer chain via Monte Carlo simulations. 24,33,35,36 The coil-helix transition has also been investigated by off-lattice Monte Carlo simulations. 20,37 In contrast, lattice Monte Carlo simulations of the coil-helix transition are rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, much attention has been paid to the coil-globule transition of a polymer chain via Monte Carlo simulations. 24,33,35,36 The coil-helix transition has also been investigated by off-lattice Monte Carlo simulations. 20,37 In contrast, lattice Monte Carlo simulations of the coil-helix transition are rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of the coloring scheme for preparing PLCs suggested by Khokhlov and coworkers, ,, several experimental studies have been conducted aimed at synthesizing random copolymers with tunable monomer sequence distributions (RCPs). Recently Genzer and coworkers synthesized poly(styrene- co -4-bromostyrene) (PBr x S) RCPs by brominating polystyrene (PS) in solvents with varying degree of solubility. Whereas bromination below the theta temperature of the parent homopolymer resulted in the formation of blocky PBr x S RCPs, bromination above the theta temperature resulted in the formation of random PBr x S RCPs.…”
Section: Introductionmentioning
confidence: 99%
“…Their study revealed that for a fixed copolymer molecular weight, block copolymers were the best interfacial compatibilizers, but longer random copolymers outperformed shorter block copolymers in reducing the interfacial tension between incompatible homopolymer phases. Since the introduction of the coloring scheme for preparing PLCs suggested by Khokhlov and coworkers, [1][2][3]18,19 several experimental studies have been conducted aimed at synthesizing random copolymers with tunable monomer sequence distributions (RCPs). [20][21][22][23][24][25][26][27][28] Recently Genzer and coworkers 28 synthesized poly(styrene-co-4-bromostyrene) (PBr x S) RCPs by brominating polystyrene (PS) in solvents with varying degree of solubility.…”
Section: Introductionmentioning
confidence: 99%
“…These copolymers could form dense globules in special solvents. Khokhlov has synthesized the “protein‐like” copolymers and studied their properties especially in self‐assembly 2–8. The protein‐like copolymer consists of two types of monomer units: hydrophobic (H) and polar (P) ones.…”
Section: Introductionmentioning
confidence: 99%
“…Khokhlov has synthesized the ''protein-like'' copolymers and studied their properties especially in selfassembly. [2][3][4][5][6][7][8] The protein-like copolymer consists of two types of monomer units: hydrophobic (H) and polar (P) ones. It was observed that such protein-like copolymers could form dense globular conformation, in which all the H-units are in the core while P-units form the envelope of this core.…”
Section: Introductionmentioning
confidence: 99%